Metáforas orientacionales y espacialización del sujeto en Una casa en la sombra, de Carlos López Degregori - Fernández Cozman, Camilo (2018)
Based on the contributions of the cognitive linguistics of George Lakoff and Mark Johnson, and the approaches of Michel Collot, María Lucía Puppo and Alicia Salomone, the author analyzes the orientational metaphors and the spatialization of the subject in Una casa en la sombra, third book of poems by Carlos López Degregori. Lakoff and Johnson distinguish structural metaphors,  ontological and orientational metaphors from the idea that human thought is, to a large extent, metaphorical. Collot points out how the modern poet projects his subjectivity in external spaces. This notion is developed by Puppo and Salomone in order to characterize the pact of the poet with modernity.